Network Analysis in Tourism Distribution Channels - Jeeva, Ananda; Tran, Mai (Atlantis Press, 2014)
Application of Network Analysis in tourism research is relatively new, especially in the study of tourism distribution channels. Network Analysis is employed to investigate the structure and pattern of relationships between actors in anetwork. This paper applies Network Analysis with ORA software to analyze tourism distribution channels. The results of the research show the pattern of the network between tour operators and travel agencies and between tour operators. Network Analysis also reveals the cooperation and cohesion of the network as well as the network dynamics between the case study tour operator and its travel agencies over a period of time.